1972
DOI: 10.1007/bf02360112
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis in free-living lechwe antelope in Zambia

Abstract: The Kafue lechwe population of Zambia numbers 90,000 and is divided by the River Kafue into two virtually segregated populations. The south bank population is known to be infected with tuberculosis but the north bank is thought to be free. One hundred and twenty-five south bank lechwe were cropped at random and lesions of tuberculosis were found in 45 (36 %). Isolates from lung lesions were typed as Mycobacterium tuberculosis vat. boris.Twenty-five of 27 pneumonia cases appeared active and on the assumption th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 2 publications
0
30
1
1
Order By: Relevance
“…Other reports have attributed the high prevalence of BTB in cattle in the Kafue basin to the contact that exists between cattle and wild animals, particularly the lechwe antelopes (Cook et al, 1996;Cosivi et al, 1998;Pandey, 1998;Sitima, 1997). Some reports have described the Kafue lechwe antelope as a reserviour/source of source of an un-treatable BTB (Gallagher et al, 1972;Pandey, 1998;Stafford, 1991). Pandey (1998) postulated that cattle on the plains could acquire BTB through grazing contaminated pastures (Pandey, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have attributed the high prevalence of BTB in cattle in the Kafue basin to the contact that exists between cattle and wild animals, particularly the lechwe antelopes (Cook et al, 1996;Cosivi et al, 1998;Pandey, 1998;Sitima, 1997). Some reports have described the Kafue lechwe antelope as a reserviour/source of source of an un-treatable BTB (Gallagher et al, 1972;Pandey, 1998;Stafford, 1991). Pandey (1998) postulated that cattle on the plains could acquire BTB through grazing contaminated pastures (Pandey, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is a gregarious medium sized semi-aquatic antelope living in very large groups that become further concentrated during the rainy (due to floods) and dry season (due to limited grazing and watering points). It has been reported to share water and grazing pasture with cattle during the drier months of the year (Gallagher et al, 1972). When pasture grounds dwindle due to aridity and watering points remain few, the grazing range of cattle and lechwe antelopes overlap and the two animal species interact through congregating at few remaining watering points and thus facilitating possible transmission through the contamination of pasture and water sources.…”
Section: Introductionmentioning
confidence: 99%
“…27 Lechwe numbers in the early 1970s were estimated around 90 000 animals. 15 Surveys indicated that significant population declines in these antelope have been ongoing since the 1970s. 27 Other wildlife species known to be infected with BTB in South Africa's national parks include lions (Panthera leo), cheetahs (Acinonyx jubatus), chacma baboons (Papio ursinus), greater kudu (Tragelaphus strepsiceros), leopards (Panthera pardus), hyenas (Crocuta crocuta), large-spotted genets (Genetta tigrina), warthogs (Phacochoerus aethiopicus), bushpigs (Potamochoerus porcus), and eland (Taurotragus oryx); however, most or all of these animals-with the possible exception of the kudu-appear to be secondary dead-end hosts at this time.…”
Section: African Buffalo and Lechwe In Parks In Africamentioning
confidence: 99%
“…No cases of BTB were found in juvenile animals younger than 18 months. 15 Surveillance. Surveillance for BTB in Kruger National Park has been ongoing for several decades.…”
Section: African Buffalo and Lechwe In Parks In Africamentioning
confidence: 99%
“…Nevertheless, published information seems to indicate that bTB is probably widespread in livestock at the continental level [32,33], whereas bTB infection of wildlife has only been confirmed in few countries of southern and eastern Africa [13,21,34].…”
Section: Regional Contexts For Btb In Wildlife In Africa Overviewmentioning
confidence: 99%